RSV attributable mortality in Portugal between 2014 and 2018 - Rodrigues, Ana Paula (2019)
Background: Respiratory Syncytial Virus (RSV) has been recognized as a serious pathogen in at-risk adult populations (long-term care facilities, immunocompromised). In adults, RSV infection is usually mild, but its effect on morbidity and mortality in adults can be substantial as has been previously reported (1). Given RSV has a similar seasonality pattern as influenza virus it is plausible that RSV circulation had contributed to excess all-cause mortality observed during previous winters in Portugal. This study aimed to estimate RSV attributable all-cause mortality between 2014/15 and 2017/18 autumn-winter seasons in Portugal.